Pulmonary Pathology of End-Stage COVID-19 Disease in Explanted Lungs and Outcomes After Lung Transplantation. Issue 6 (6th January 2022) - Flaifel, Abdallah; Kwok, Benjamin; Ko, Jane; Chang, Stephanie; Smith, Deane; Zhou, Fang; Chiriboga, Luis A; Zeck, Briana; Theise, Neil; Rudym, Darya; Lesko, Melissa; Angel, Luis; et al.
Abstract: Objectives: Patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may develop end-stage lung disease requiring lung transplantation. We report the clinical course, pulmonary pathology with radiographic correlation, and outcomes after lung transplantation in three patients who developed chronic respiratory failure due to postacute sequelae of SARS-CoV-2 infection. Methods: A retrospective histologic evaluation of explanted lungs due to coronavirus disease 2019 was performed. Results: None of the patients had known prior pulmonary disease. The major pathologic findings in the lung explants were proliferative and fibrotic phases of diffuse alveolar damage, interstitial capillary neoangiogenesis, and mononuclear inflammation, specifically macrophages, with varying numbers of T and B lymphocytes. The fibrosis varied from early collagen deposition to more pronounced interstitial collagen deposition; however, pulmonary remodeling with honeycomb change was not present. Other findings included peribronchiolar metaplasia, microvascular thrombosis, recanalized thrombi in muscular arteries, and pleural adhesions. No patients had either recurrence of SARS-CoV-2 infection or allograft rejection following transplant at this time. Conclusions: The major pathologic findings in the lung explants of patients with SARS-CoV-2 infection suggest ongoing fibrosis, prominent macrophage infiltration, neoangiogenesis, and microvascular thrombosis. Characterization of pathologic findings could help develop novel management strategies.